Radiographic evaluation of neck shaft angle ( nsa ) remodelling following varus osteotomy of proximal femur in children - Amir Osman, Normawathy (2013)

(untitled)
Introduction :The neck shaft angle of the proximal femur following varus osteotomy will change towards its normal NSA angle for the age. This study was conducted to find the changes of proximal femur following varus osteotomy in children within first three years. Patients and Methods: This was a retrospective study conducted on 22 femurs following varus osteotomy. The neck shaft angle measurement was done on pelvic radiograph on PAC system. The point of assessments were at pre-operative, immediate post operative, end of one year, end of second year and end of third year post operative. Results:. The patients were between age of 1 year 10 months till 10 year 10 months ( mean age : 5 year 6 months ). Amount of additional varus created between 110 to 660 with mean of 31.20 . The range of NSA created by the surgery was between 930 and 1360 with mean of 115.680. In the first year after osteotomy, out of 22 hips , NSA decreased in 9 hips and increased in other 13 hips ( 59.1 % ) . In the second year after osteotomy NSA increased (between 20 and 17˚) in 14 out of 16 hips . At year three after surgery NSA increased (between 20 Pearson correlation analysis of 13 hips with increase of NSA at one year after osteotomy showed a strong positive correlation (r=0.455) between amount of additional varus and remodelling.